Pengaruh Kecepatan Putar dan Jumlah Masukan Batang Singkong Terhadap Kinerja Mesin Rabakong Tipe TEP-6 - Asmara, Sandi; Kuncoro, Sapto; Suharyatun, Siti; Juliantoro, Rizky Alif (Jurnal Agricultural Biosystem Engineering, 2023)
Cassava production not only produces tubers, but also produces waste, one of which is cassava stems. So far, the waste of cassava stems has not been widely used by farmers, so that after the cassava is harvested, the cassava stems are just left lying on the ground. This study aims to reduce cassava stem waste through size reduction using a cassava stem chopper (Rabakong) with variations in engine speed per minute (RPM).This research was carried out at the Agricultural Equipment and Machinery Power Laboratory, Department of Agricultural Engineering, Faculty of Agriculture, University of Lampung in May - June 2023. The treatment used 3 variations of RPM namely 800, 1000, and 1400 where each used 3 different amounts of input, and each RPM was repeated 3 times. The number of inputs used is the input of 3 sticks, 4 sticks, and 5 sticks. The results showed that chopping using the RPM setting of 1400 and the input amount of 4 cassava sticks had the best working capacity with a value of 194.448 kg/hour. Lowest fuel consumption by using the RPM setting of 800 and the number of inputs of 3 sticks with a value of 1,073 liters/hour. Keywords:  Cassava Stems, Input, Rabakong, RPM.